Poster 151: Latarjet Treatment of Anterior Shoulder Instability: The Effect of Pre-Operative MRI Coracoid Dimensions on Post-Operative Outcomes. Issue 7 (30th July 2022) - DeBernardis, Dennis; Hameed, Daniel; Clements, Ari; Kamel, Sarah; Freedman, Kevin; Bishop, Meghan; Paul, Ryan
Objectives: While pre-operative coracoid dimensions have been previously evaluated utilizing CT, no studies have utilized MRI to evaluate coracoid dimensions before Latarjet surgery. Also, no studies have evaluated post-operative outcomes based on pre-operative coracoid dimensions in Latarjet patients. Therefore, the purpose is to determine the effect of coracoid length and width as measured on pre-operative imaging (MRI) on outcomes following Latarjet treatment of anterior shoulder instability. We hypothesized that patients with longer and wider coracoid dimensions would have improved post-operative outcomes after Latarjet treatment for anterior shoulder instability. Methods: Patients who underwent primary Latarjet surgery between 2009-2019 were identified. Inclusion criteria were an available pre-operative MRI and minimum of 2-year post-operative follow-up. Longitudinal coracoid length was measured on axial MRI sequences as the distance from the coracoclavicular ligament insertion to the distal tip. Width measurements were obtained perpendicular to length at three locations – the coracoid base, midpoint and tip – and then averaged. Inter-rater reliability was good for measuring both coracoid length (ICC=0.75) and coracoid width (ICC=0.76). The primary outcomes of interest were recurrent instability, re-operation, complications, rate of and time until return-to-sport (RTS), and American Shoulder and Elbow Surgeons (ASES) score. Comparisons were made between shorter vs. longer coracoid length, narrower vs. wider coracoid width, and male vs. female coracoid dimensions. Results: 56 patients were included with an average age of 28.4 years and 16% were female. There were no statistically significant demographic differences between coracoid length and coracoid width groups. Coracoid length averaged 21.6 ± 2.4 mm (range: 16.7-26.9 mm), coracoid width 10.0 ± 1.0 mm (range: 8.3-13.2 mm), and glenoid bone loss 13.7% ± 8.2% (range: 0.0%-32.4%). There were 41 patients (73.2%) with harvestable coracoid length ≥ 20 mm. 55 patients received two coracoid screws for fixation, and only one patient was limited to one screw. Patients with a smaller coracoid length (<22 mm, n=30) had similar rate of recurrent instability (smaller length 6.7% vs. longer length 3.8%), complication (10.0% vs. 15.4%), re-operation (3.3% vs. 7.7%), rate of RTS (76.5% vs. 58.8%), and post-operative ASES scores (85.0 vs. 81.6) (all p>0.05), relative to patients with a larger coracoid length (>22 mm, n=26). Likewise, patients with a smaller coracoid width (<10 mm, n=29) had similar prevalence of recurrent instability (smaller width 6.9% vs. larger width 3.7%), complication (17.2% vs. 7.4%), re-operation (3.5% vs. 7.4%), rate of RTS (66.7% vs. 68.4%), and post-operative ASES scores (87.1 vs. 80.0) (all p>0.05), relative to patients with a larger coracoid length (>10 mm, n=27). Finally, male patients had a larger average coracoid width (10.1 ± 1.0 mm) than female patients (9.3 ± 0.5 mm) (p=0.001). Conclusions: This MRI protocol closely accounts for the specific landmarks utilized during the Latarjet osteotomy by focusing on identification of the CC ligament insertion. A minimum pre-operative coracoid length of 25 mm is not needed as previously stated, as anterior shoulder instability patients experience favorable post-operative outcomes after Latarjet surgery regardless of pre-operative coracoid dimensions based on our findings. Surgeons who are treating patients with significant glenoid bone loss may utilize this MRI protocol if they are concerned about the anatomy of the coracoid pre-operatively. Figure 1. Demonstration of coracoid width measurements. (Figure 2A) First, on the coronal T1 weighted oblique sequence the coracoclavicular ligaments were identified (between the red arrows), outlined by fat, including the more medial trapezoid ligament and lateral conoid ligament. (Figure 2B) Using scout localizers, the insertion of the coracoclavicular ligaments on the fluid sensitive axial sequence was identified (red arrow). A line from this point to the anterior margin of the glenoid was drawn (yellow dotted line) denoting the width of the coracoid base. Coracoid width measurements were then collected at three locations: 5 mm anteriorly from the coracoid base, midpoint, and 5 mm posteriorly from the coracoid tip. A straight line from the midpoint of the base to tip (not shown) was drawn to approximate coracoid length. Figure 2. Difference between mean pre-operative coracoid length (on left) and width (on right) between female (dark) and male (not dark) patients as measured on MRI. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/d06d5b2e-8ec8-40b2-a9b0-fd58358533b7/1/Table_2_Coracoid_Dimensions.doc Table 1. Comparison of post-operative complications, recurrent instability, and re-operation between smaller (<22 mm) and larger (≥22 mm) coracoid length, and between smaller (<10 mm) and larger (≥10 mm) coracoid width. Categorical data presented as n (%), continuous data presented as mean ± standard deviation. Table 2. Comparison of post-operative American Shoulder and Elbow Surgeons (ASES) scores, return to play (RTP) rates, and RTP time between smaller (<22 mm) and larger (≥22 mm) coracoid length, and between smaller (<10 mm) and larger (≥10 mm) coracoid width. Categorical data presented as n (%), continuous data presented as mean ± standard deviation.